ANALISIS KESEIMBANGAN TERMAL PADA AREA PAMER MUSEUM GEOLOGI BANDUNG - Gunawan, Grace (SENADA (Seminar Nasional Manajemen, Desain dan Aplikasi Bisnis Teknologi), 2018)
Bandung is one of the cities that inherited a lot of colonial buildings, especially Dutch colonial buildings. This colonial building is known for its excellent thermal comfort, but since the industrial revolution, the number of greenhouse gases has increased in the atmosphere and caused global warming leading to climate change. This climate change happens to make the annual average temperature increase in Bandung. Hot air coming from outside the building goes into the room and causes the temperature in the room increases. Apart from the heat sources from indoors, there are also sources of heat coming from the exterior, such as electronic equipment, humans, etc. The purpose of this study is to improve the thermal conditions and as initial research to make energy savings in the Museum of Geology. In this study, the exhibition area of the selected Museum Geologi is the exhibition area on the 1st floor of Geological Museum, the four rooms are still not renovated as in the exhibition area on the 2nd floor. The method used in this research is the thermal balance method, where in this method any good heat source from outside the building is calculated.